2009
DOI: 10.1007/s11695-009-9885-8
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Rapid Airway Management Positioner in Obese Patients Undergoing Gastric Bypass or Laparoscopic Gastric Banding Surgery

Abstract: A new positioning device, the Rapid Airway Management Positioner (RAMP, Airpal Inc., Center Valley, PA) was evaluated to determine if there was an improvement in either mask ventilation, direct laryngoscopy, or both with the use of the RAMP in this patient population. Fifty-one morbidly obese patients (BMI > 35 kg/m(2)) undergoing elective bariatric surgery were enrolled. Ventilation and laryngoscopy was performed in the neutral and head-elevated laryngoscopy position (HELP). Direct laryngoscopy was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
1
35
0
1
Order By: Relevance
“…Various methods and degrees of head elevation have been described for intubating OR patients [3][4][5], [7][8], difficult ED patients [6], patients undergoing awake intubation [10], and even simulated patients in an ambulance setting [11]. Nevertheless, traditional supine intubation remains widespread and upright intubation remains underrepresented in research and in medical education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various methods and degrees of head elevation have been described for intubating OR patients [3][4][5], [7][8], difficult ED patients [6], patients undergoing awake intubation [10], and even simulated patients in an ambulance setting [11]. Nevertheless, traditional supine intubation remains widespread and upright intubation remains underrepresented in research and in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…Live tissue in real patients is affected by gravity differently than mannequins. However, previous studies have suggested that head elevation may decrease the force of gravity on live tissues, indicating that the anatomic advantages of upright position would likely be important in live patients [4], [6], [7].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When using patients as their own controls and comparing laryngoscopy in both 'ramped' and 'sniffing' position, the former provides improved or unchanged views of the larynx in 88% of patients with BMI less than 25 kg m À2 , in 91% in patients with BMI higher than 30 kg m À2 and in 100% of patients with BMI higher than 45 kg m À2 . 12 The use of a premanufactured elevation pillow, 13 or an inflatable pillow, 14 instead of blankets can improve both view of the larynx and mask ventilation. During surgery, the inflatable pillow can be deflated, bringing the patient back to the supine position.…”
Section: Preinductionmentioning
confidence: 99%
“…42 It should follow a planned strategy and logically should be performed in the same 'ramped' position used for intubation. This is not easy to do in an anaesthetised patient without the inflatable pillow, 14 or an operating table that can be suitably configured.…”
Section: Emergence and Extubationmentioning
confidence: 99%